Influence of NPM, PBV, DER, TATO, and EPS on Stock Prices of Automotive Sub Sector Companies and Its Components Listed on IDX in 2014 - 2018 - Della Chairini Ibrahim; Harry Patuan Panjaitan (Journal of Applied Business and Technology, 2020)
This study aims to determine the effect of Net Profit Margin, Price Book Value, Debt to Equity Ratio, Total Asset Turnover, and Earning per Share on the Stock Prices of Automotive and Components sub sector companies listed on Indonesia Stock Exchange in 2014 - 2018. Purposive sampling method was used to obtain samples of 12 out of 13 companies as the population. The research method used was multiple linear regression analysis techniques using SPSS 19.0. The results of this study indicate that partially, the Net Profit Margin, Debt to Equity Ratio and Total Asset Turnover variables have no effect on the Stock Price, while the Price Book Value and Earning per Share variables have an influence on the Stock Price. Simultaneously, all independent variables have an influence on stock prices.